Supporting Digital Self-Assessment through Universal Design for Learning (UDL): (Instructor’s Reflective Practice in a Graduate Course in Higher Education) - Jamilah Mohammed Alamri (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
This study aims to focus on the process of UDL implementation and the reflective practice of an instructor based on the collaborative work with the researcher (author of this paper) when redesigning a graduate course in a face-to-face and Blackboard (Bb) environment in a higher education university. Participatory action research was employed to document the design of a UDL course using multiple instruments. Three experts evaluated the course and its adherence to UDL framework both in Bb and face-to-face classrooms using the UDL Observation Measurement Tool (UDL-OMT). Forty-three students filled out a survey about their perceptions of the course and whether it aligned with UDL principles. Students’ reflections on how the UDL course influences their success in the course were collected after the course had ended. Experts found that UDL implementation was more prevalent in a Bb environment than in a face-face environment. Students indicated that digital self-paced ungraded self-assessments were the most useful strategy, and that the action and expression principle was the most prevalent in the UDL designed course. Qualitative analysis revealed five themes that illustrate students’ positive perceptions of how the UDL course influenced their success such as increased comprehension, reduced stress & anxiety, democratised culture of learning, diverse learning pathways, and disambiguated learning arena. This study contributes to fill the gap of applying action and expression principles using digital technology and self-paced and ungraded self-assessments besides other useful strategies. Future research and recommendations in light of the results are explained in the study.